Implementing Remote Memory Clinics to Enhance Clinical Care During and After COVID-19 - Owens, Andrew P.; Ballard, Clive; Beigi, Mazda; Kalafatis, Chris; Brooker, Helen; Lavelle, Grace; Brønnick, Kolbjørn K.; Sauer, Justin; Boddington, Steve; Velayudhan, Latha; Aarsland, Dag (Frontiers in Psychiatry, 2020)
Social isolation is likely to be recommended for older adults even after COVID-19 restrictions are lifted, with ongoing reduced clinical contact suggested for this population. This has increased the need for remote memory clinics. Here we review the literature, current practices and guidelines on organising such remote memory clinics, focusing on assessment of cognition, function and other relevant measurements, proposing a novel pathway based on three levels of complexity: from simple telephone or video-based interviews and testing using available tests (Level 1), to digitized and validated methods based on standard pen-and-paper tests and scales (Level 2) and finally discuss the use of fully digitized cognitive batteries and remote measurement technologies (RMTs, Level 3). Utilising online cognitive testing can provide more accurate measures of cognitive status and RMTs also offer a ‘real-time’ window into functional status of the patient. Pros and cons of these strategies are discussed. Remotely collected data negates the need for frail patients or carers to commute to clinic and offers valuable insights into progression over time, as well as treatment responses to therapeutic interventions, providing a more realistic and contextualised environment for data-collection. Notwithstanding several challenges related to internet access, computer skills, limited evidence base and regulatory and data protection issues, digital biomarkers that can be collected remotely have significant potential for diagnosis and symptom management in older adults and we propose a framework and pathway for how technologies can be implemented to support the remote memory clinic. These platforms are also well-placed for administration of digital cognitive training and other interventions. The individual, societal and public/private costs of COVID-19 are high and will continue to rise for some time but the many challenges the pandemic has placed on memory services also provides an opportunity to embrace novel technologies and approaches. Remote memory clinics can be cost-saving and their financial, logistical, clinical and practical benefits have been highlighted by COVID-19, supporting their use to not only be maintained when social distancing legislation is lifted but to be devoted extra resources and attention to fully potentiate this valuable arm of clinical assessment and care.